The education policy around the massification of higher education and its relationship to university dropout in Colombia - Guerrero, Sara Cristina; Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper contextualizes the policies around the dropout phenomenon derived from the processes of massification of the highereducation, university reforms, standards on a global scale established by the international organisms, neoliberal policies and the regulations given by the World Trade Organization. These regulations imposed the university model of the 21st century; where education, as a service, focuses on the cost-benefit and on the calculation of monetary losses. The purpose of this work is to understand the interest in the emergence of national policies around university dropout. Through a documentary review, focused on quality, coverage, effectiveness and inclusion, and taking into account the regulations given by international organizations, based on the Millennium Development Goals, Sustainable Development Goals, main conferences on Higher Education, World Declaration Education for All (Jomtien); Dakar Framework for Action and the Incheon Declaration. Subsequently, we describe their influence on development plans (1998-2018), decennial education plans. Finally, it is concluded that there exist contradictions between what is indicated in a policy of expanding coverage and investment in higher education, vs. a reality of budget cuts that moves away from achieving the social welfare policy, as a strategy to fight university dropout that alleviates the initial academic inequality, and the socio-economic problems of the Colombian university student population.